The Tsukamoto Fuzzy Method for Predicting the Availability Status of Goods Inventory Based on Identification with RFID Technology - Arif Sungkono; Dewi Handayani Untari Ningsih (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
Data collection of goods entering and leaving the warehouse is very important. However, in large companies with hundreds of items being traded, manual recording can take a long time. To solve this problem, an RFID reader is used to record the name of the goods in the warehouse. By using RFID, the recording time can be reduced. Combined with the application of the Tsukamoto fuzzy algorithm, the system can predict the amount of inventory in the coming month to create sufficient inventory or not excess or less and the company can obtain optimal profits due to the process of buying and selling goods. This study aims to create an inventory system that can record goods through scans and can predict inventory in the coming month. The method used in this research is RFID technology and the Fuzzy Tsukamoto method. The results of this study indicate that the application can scan incoming or outgoing goods tags using RFID technology. The system can also predict the amount of inventory in the coming month using the Tsukamoto fuzzy method.